Is yoga an effective modality of stress reduction within medical population; a qualitative study within MBBS students of BRD medical college, Gorakhpur - Tiwari, Vikash K.; Singh, Vinay; Kumar, Devesh; Mittal, Mahim; Asthana, A. B. (International Journal of Research in Medical Sciences, 2018)
Background: Stress is very common in medical professionals. Stress begins in the first year of medical school and increases with subsequent years of medical life. Stress decreases overall performance and had a multitude of health-related adverse effect. Yoga has been tried as a stress reduction technique in different populations. In present study yoga was performed in the 1st year MBBS students and impact on stress reduction was studied using PSS-10 stress scale. Methods: Study groups, yoga and control contained 26 and 27 subjects respectively. The yoga group practiced selected yogic asana, pranayama, and yoga nidra 1hour daily 6days a week for 3months. Control group kept in touch and allowed their usual activity as before. The PSS-10 scale used to measure the level of stress in both groups pre and post study. Results: There was a highly significant reduction in the PSS-10 Score (stress level) in the yoga group (P Value <0.0001) but there was no significant change in the PSS-10 Score of control group (P Value = 0.2930). Conclusions: Yoga is an effective modality of stress reduction technique in 1st year medical students. Therefore, yoga should be introduced as a part of the curricula in the first year of medical school. This may be taken as the 1st step in implantation of healthy lifestyle in future health care providers.